Virtual Assistants LLMs and pattern making: an intersection of artificial intelligence and the textile industry - Silva, José Heitor da; Teixeira, Júlio Monteiro (DAT Journal, 2026)
In contemporary times, ChatBots (virtual assistants) such as ChatGPT and Microsoft Copilot are emerging as promising tools for optimization and learning, driven by technological innovations. The textile industry, like other sectors, seeks to combine human expertise with the innovative potential of technology. Within this context, studies on pattern making in fashion have gained prominence in the digital environment. This qualitative and exploratory work aims to analyze the results of searches on ChatBots about the execution orders of pattern making diagrams for fashion products. The analysis of the responses from ChatGPT and Microsoft Copilot, specifically in pattern making diagramming, revealed that, despite the advances in artificial intelligence, the presence of a critical and investigative human eye remains essential to identify and correct inaccuracies in the information generated. This highlights the need for solid prior knowledge in the area to validate the accuracy of the results and ensure quality in the pattern creation process.